Stop moving! Pain, body and trauma in pictures and narratives of patients, suffering with a somatoform disorder. (26th July 2021) - Ruettner, Barbara; Zander, Michael; Kappler, Melanie; Niehaus, Johanna; Thomas, Nele; Kaiser, Paul Maximilian; Goetzmann, Lutz
Abstract: Somatoform pain disorders are strongly associated with adverse, mostly traumatic childhood experiences. Little is known, however, about the psychodynamic background, for example, with regard to defence, affect regulation, and traumatic representations. As part of a qualitative study in which 13 patients with somatoform disorder were investigated, we compared the interviews and drawings by the two patients which featured the most pictorial codes for deaffectualization as a defence of the autistoid type of early disorders with the two patients that displayed the fewest codes for deaffectualization. These patients suffered from a more mature, non‐autistoid disorder. The drawings were analyzed according to the Visual Grounded Theory, the interviews according to Content Analysis. We used the qualitative atlas.ti‐software. In the two patients with a high evidence of pictorial deaffectualization, a correspondence was found between the deaffectualization and the type of pain sensation: Physical movements led to an increase in pain. The affective as well as the physical rigidity may have been intended to avoid the body image's fragmentation. The drawings by the more mature patients showed strong, partly violent interactions. In the narratives, the patients tended more to report feelings of agitation; generally, more physical movements could be allowed. In all four patients, a considerable correspondence was identified between the drawings and the narratives about physical pain. The dimension of the imaginary was determined both physically (on the level of the body image) and pictorially (on the level of the mental image) through the regulation of traumatic affects.